The effect of liquid glass on the deformation of refractory binder/Skystojo stiklo įtaka kaitrai atsparaus rišiklio deformacijoms - Antonovič, Valentin; Goberis, Stasys (Journal of Civil Engineering and Management, 2001)
The structure formation of a refractory binder of liquid glass, ferrochrome slag and dispersed chamotte has been studied. It has been found that there is a close relationship between the density of liquid glass used and sharp expansion of binder at the temperature of 500–600 °C: the lower the density, the lower the expansion of the material. To find the reason for this deformation of a binder, the specimens of dried out liquid glass (sodium hydro silicates) heating tests (Fig 1) and the specimens of dried out mixtures of liquid glass and some inert refractory materials (Table 2) dilatometric tests (Fig 2) have also been made. This investigation showed that sodium hydro silicates films bloated during heating. In order to determine structural changes under high temperature, X-rays investigation of refractory binder was made (Fig 5). This investigation showed that the reaction at the solid phase starts at the temperature over 600 °C and had no effect on the deformation of binder at 500–600 °C. It has been shown that the deformations occurring at 500–600 °C are caused by bloating of sodium hydro silicates (non-reacted liquid glass during hardening) films of the binder. Article in Lithuanian. First Published Online: 30 Jul 2012